Sistem Pendukung Keputusan Seleksi Beasiswa Situbondo Unggul Menggunakan Metode Simple Additive Weighting dan Profile Matching - Moh Febri Nurul Qorik; Slamin Slamin; Priza Pandunata (Faculty of Computer Science, University of Jember, 2018)
This study is about the use of simple additive weighting (SAW) and profile matching methods for the construction of information systems supporting the decision selection of scholarships. The case study of this research is the selection of superior situbondo scholarships in the Education Office of Situbondo Regency. The purpose of this study was to apply the profile matching method and SAW in resolving the problem of selecting the Situbondo Superior Scholarship recipients who had 2 aspects of assessment, namely aspects of poverty and academics which made it difficult to select scholarships, this difficulty is caused by the value of the aspect of poverty must be the smaller the difference in the value of students with the value of the scholarship it will be better while the academic value must go far beyond the minimum value, the better. The profile matching method is used to calculate the value of the aspect of poverty and SAW is used to calculate the value of the academic aspects. To determine the final results of this study using the criteria for decision-making scale determined by the District Education Office of Situbondo, one of the final methods of the method is less than 30 worth not funded, one of the final method values less than 60 is considered to be funded. The development of information systems supporting superior decision making for the Situbondo scholarship using the profile matching and simple additive weighting methods using a website-based system with system design using the SDLC waterfall model, implementation of the system using the laravel framework and program code using the hypertext pre-processor programming language (PHP ), while for managing the database using MySQL DBMS and system testing using black box and white box ( testing unit). The results of this research method of profile matching and simple additive weighting can be applied properly in a superior situbondo scholarship decision support system.